THE INFLUENCE OF PARENTS INCOME AND PEER FRIENDS SUPPORT ON STUDENTS STUDY INTENTION FROM COLLEGE STUDENTS AT RAANAN BARU - Maria Amelia Carmelita Tumewu; Joy E. Tulung; Maria V. J. Tielung (Universitas Sam Ratulangi, 2023)
In this era, there are many factors that influence students' study intention, especially for college students. In this study, the object is college students at Raanan Baru and the factors in this study that influence student study intention are parents income and peer friends support. The purpose of this research is to analyze the influence of parent’s income and peer friends support on students study intention partially and simultaneously. This research use quantitative method with data collection using questionnaire with Likert scale method was processed in SPPS application, multiple linier regression as the tool of analysis. The sample of this study is 60 respondent. Based on the results of research, the parent’s income and peer friends support influence students study intention from from college students at Raanan Baru. Keywords: parents income, peer friends support, students study intention